IMPACT OF ROMANIAN PHYSICAL EDUCATION POLICY ON YOUTH HEALTH OUTCOMES: A SECONDARY DATA ANALYSIS (University Arena, 2025)
Background and aims: this comprehensive investigation explores how regional disparities in mandated physical education (PE) instructional time influence two critical health outcomes in Romanian adolescents: obesity prevalence and self-reported moderate to vigorous physical activity (MVPA) rates. Amid growing public health concerns regarding childhood obesity and declining physical activity levels, Romania presents a valuable context due to substantial inter-county variations in education policy implementation. The aim was to determine whether counties with greater weekly PE exposure report better health outcomes among adolescents, adjusting for socioeconomic differences.Methods: we utilized publicly accessible secondary datasets, compiling county-level weekly PE time from UNESCO’s Global Education Monitoring Report (2021), adolescent health indicators from the WHO European Health Information Gateway (2023), and contextual covariates, average disposable household income and urbanization percentages, from Eurostat and the Romanian National Institute of Statistics (INS, 2023). The dataset covered all 42 administrative counties. Statistical procedures included Pearson correlation to assess bivariate relationships, descriptive analyses to summarize distributions, and multivariate linear regression models to isolate the effect of PE time while adjusting for income and urbanization. Results: findings revealed a statistically significant moderate inverse correlation between PE time and obesity prevalence (r = –0.38, 95% CI [–0.60, –0.10], p = 0.015) and a moderate positive correlation with MVPA rates (r = 0.44, 95% CI [0.17, 0.65], p = 0.006). Multivariate regressions confirmed that each additional 10 minutes of weekly PE is associated with a 0.7 percentage-point decrease in obesity prevalence (β = –0.07, p = 0.004) and a 0.9 percentage-point increase in MVPA participation (β = 0.09, p = 0.002), independent of regional income or urban development level.Conclusions: these results underscore the importance of standardized and sufficient PE provision in shaping adolescent health across Romania. Findings are discussed within the context of established pain management and injury prevention frameworks in youth sports and evidence-based strategies for body weight control. This study offers critical insight into how curricular time allocations can  produce measurable health benefits and argues for policy reform to harmonize PE standards nationwide. Additionally, implications are explored for education authorities, public health planning, and targeted interventions in underserved regions.
Keywords: physical education policy; adolescent obesity; youth; health